(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The information about locations and ecologic peculiarities of nine new for Crimea peninsula species of lichens (Bryoria nadvornikiana (Gyeln.) Brodo & D. Hawksw., Buellia erubescens Arnold, Catillaria pulverea (Borrer) Lettau, Lecanora persimilis (Th.Fr.) Nyl., L. saligna (Schrad.) Zahlbr., Lepraria rigidula (B. de Lesd.) Tønsberg, Megalaria pulverea (Borrer) Haf. & Schreiner, Micarea misella (Nyl.) Hedl., Pertusaria pupllaris (Nyl.) Th. Fr.) are provided.